An introduction to medieval theology. - Van Nieuwenhove, Rik, 1967- (Cambridge Cambridge university press, 2012)
"An Introduction to Medieval Theology Medieval theology, in all its diversity, was radically theo-centric, Trinitarian, Scriptural, and sacramental. It also operated with a profound view of human understanding (in terms of intellectus rather than mere ratio). In a post-modern climate, in which the modern views on "autonomous reason" are increasingly being questioned, it may prove fruitful to re-engage with pre-modern thinkers who, obviously, did not share our modern and post-modern presuppositions. Their different perspective does not antiquate their thought, as some of the "cultured despisers" of medieval thought might imagine"--Provided by publisher.
Machine generated contents note: 1. Introduction; Part I. The Legacy of the Fathers: 2. Augustine of Hippo; 3. Monks and scholars in the fifth and sixth centuries: John Cassian, Boethius and Pseudo-Dionysius; Part II. Early Medieval Theologians: 4. Gregory the Great; 5. John Scottus Eriugena; Part III. The Eleventh and Twelfth Centuries: 6. Introduction: renewal in the eleventh and twelfth centuries; 7. Anselm of Canterbury; 8. Monks and scholars in the twelfth century: Peter Abelard, William of St Thierry and Bernard of Clairvaux; 9. Hugh of St Victor; 10. Richard of St Victor; 11. Peter Lombard and the systematisation of theology; Part IV. The Thirteenth Century: 12. Introduction; 13. Thomas Aquinas; 14. Bonaventure; 15. The Condemnations of 1277; 16. John Duns Scotus; Part V. The Fourteenth Century and Beyond: 17. Introduction; 18. William of Ockham; 19. Meister Eckhart; 20. Jan van Ruusbroec and the Modern Devotion; 21. Epilogue; Bibliographical note; Index.
Keywords: Theology, Doctrinal -- History -- Middle Ages, 600-1500; 230.2 "04/14" -- Theologische scholen--(verder in te delen zoals 28)--Middeleeuwen